PENGARUH THEORY OF PLANNED BEHAVIOUR TERHADAP ENTREPRENEURIAL INTENTION MAHASISWA DI TANGERANG - Zoel Hutabarat (Universitas Multimedia Nusantara, 2020)
The trend of young entrepreneurs coming from students is growing and this is in line with government programs that want to introduce and create resilient young entrepreneurs from an early age. When on campus, the desire of students to build a business is huge. But when they return to the community, the number of students who want to build a business is not as big as when they were in college. This study wants to look at the impact of the presence of entrepreneurship programs at the college level on entrepreneurial intentions on students. Can the program increase the desire of students to become entrepreneurs? This research was conducted by distributing questionnaires to as many as 200 students at three private universities in Tangerang who have an entrepreneurship program and the data collected were processed using SEM PLS 3. The results of this study indicate that the variables of personal attitude, perceived behavioral control, and subjective norm, affect entrepreneurial Student intentions at the three universities studied. This can be the basis for universities to develop existing entrepreneurship programs to enhance student creativity. Not only facilitating students with exhibition programs, but also providing students with the tools to be more creative and innovative, not only in product development but also in the process of experiencing consumers. Key Words: Theory of Planned Behaviour, Entrepreneurial Iintention, Students.